The Influence of Gender and Problem-Based Learning Model on Students' Numerical Literacy in Chemistry - Yerimadesi; Andromeda; Guspatni; Fauziah; Putty Zinda Febrila; Golaleh Makrooni (Jurnal Pendidikan IPA Indonesia, 2026)
Chemical numeracy is essential for understanding quantitative concepts in chemistry; however, there are indications of achievement gaps between male and female students. This study aims to analyze the influence of gender on students' numeracy skills when implementing the Problem-Based Learning (PBL) model. This study employed a quasi-experimental design with a nonequivalent control group. The study population consisted of Phase F students at three high schools in West Sumatra, Indonesia. The sample comprised 188 students selected through purposive sampling based on initial ability equivalence. The research sample came from three schools, each serving as a research context for different topics: salt hydrolysis (experimental class = 33; control class = 30), reaction rates (experimental class = 35; control class = 35), and chemical equilibrium (experimental class = 26; control class = 29). The research instrument consisted of a chemistry numerical literacy test on reaction rates, chemical equilibrium, and salt hydrolysis, which experts had validated. Instruction in the experimental classes used the PBL model, while the control classes used conventional instruction, as typically implemented in schools. Data were analyzed using the N-gain test, normality test, homogeneity test, and Two-Way ANOVA. Results showed that improvement in numerical literacy in chemistry was greater in PBL classes than in control classes. Statistical analysis indicated that the PBL model had a significant effect on improving numerical literacy in chemistry. Gender was significant in only one school, and the interaction between the learning model and gender was also significant there, suggesting that the model's effectiveness may vary by context. These findings indicate that PBL is effective in enhancing students' numerical literacy in chemistry and imply that chemistry instruction should be designed around problem-solving approaches to develop quantitative reasoning and a contextual understanding of chemical concepts.